PENGARUH VARIASI METODE PEMBELAJARAN CERAMAH DAN TEAM QUIZ TERHADAP HASIL BELAJAR MATERI SISTEM EKSKRESI MANUSIA SISWA KELAS VIII - Dyah Visha Fauzia Ariani; HRA Mulyani; Agus Sujarwanta (EDUBIOLOCK, 2024)
This research aims to find out whether there is an influence of variations in learning lectures and team quizzes on the Human Excretory System material on the learning outcomes of class VIII students at SMP Negeri 1 Way Bungur. The research method uses an experimental research approach with a research design using a completely randomized design with three treatments with 30 replications. This research was conducted at SMP Negeri 1 Way Bungur with the research population being class VIII students. This research sample consists of one class with a sample size of 30 students. In this research, 3 learning treatments were carried out in one class. This research data collection technique uses an essay test which is used at the end of the lesson and will then be analyzed with the results of the hypothesis test. From the results of the analysis using the One Way Anova hypothesis test (Completely Randomized Design) at a significance level of 5%, it shows that Fcount = 0.027 < Ftable = 3.10 so that H0 is accepted, meaning that the lecture method, Team Quiz and lecture method accompanied by Team Quiz learning do not affect student learning outcomes. The results obtained can be concluded that the three treatments have the same quality if adjusted to each material.